2022
DOI: 10.3390/ijms23031542
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Kidney Injury and Repair

Abstract: Chronic kidney disease (CKD) will become the fifth global cause of death by 2040, thus emphasizing the need to better understand the molecular mechanisms of damage and regeneration in the kidney. CKD predisposes to acute kidney injury (AKI) which, in turn, promotes CKD progression. This implies that CKD or the AKI-to-CKD transition are associated with dysfunctional kidney repair mechanisms. Current therapeutic options slow CKD progression but fail to treat or accelerate recovery from AKI and are unable to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 220 publications
(270 reference statements)
0
35
0
Order By: Relevance
“…Abnormal expression of proinflammatory cytokines, such as IL-6 and TNF-α, in the kidney recruits associated inflammatory cells and causes inflammation in the kidney tissue. In addition, pro-inflammatory cytokines can trigger cell apoptosis and promote the synthesis of other inflammatory molecules, thus causing inflammatory response [ 23 ]. Apoptosis leads to the loss of resident kidney cells and subsequent renal injury induced by environmental and intrinsic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of proinflammatory cytokines, such as IL-6 and TNF-α, in the kidney recruits associated inflammatory cells and causes inflammation in the kidney tissue. In addition, pro-inflammatory cytokines can trigger cell apoptosis and promote the synthesis of other inflammatory molecules, thus causing inflammatory response [ 23 ]. Apoptosis leads to the loss of resident kidney cells and subsequent renal injury induced by environmental and intrinsic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to evaluate if SV40 T-ag expression affects PTEC functionality, we tested their capacity to migrate. Previous studies have shown that epithelial cells, especially after injury, exhibit a high capacity for tissue repair and regeneration compared to their healthy state in which they are mitotically quiescent 11,12 . In the kidney, this repair function is not provided by identi able stem cell populations as compared to organs with high rates of cell turnover.…”
Section: Discussionmentioning
confidence: 99%
“…However, the severity of the acute episode is not the only determinant of the progression of kidney damage. It is believed that the age of the affected person may also be important, especially in the processes of survival and resistance of kidney cells as well as the resumption of normal activity [ 40 ]. The most acute damage in kidney cells occurs in the tubular epithelial cells of the proximal S3 segment of the outer cord stripe.…”
Section: Stages In the Evolution Of Kidney Damagementioning
confidence: 99%